Parameters Affected Corrosion and Mechanical Properties of Al-Brasses - Liptáková, Tatiana; Lovíšek, Martin; Hadzima, Branislav (Manufacturing Technology Journal, 2015)
The Al-brasses are considered corrosion resistant technical materials especially used in pipe systems in energy industry. They are mostly exposed to flowing liquids environments where they are loading chemically and mechanically and their lifetime in practice condition quite vary. The aim of our research work is to compare corrosion and mechanical properties of four Al-brasses from various producers. The Al-brasses have very similar chemical composition but differ in microstructure, surface state what affect their corrosion and mechanical behavior. By chosen experimental methods and analyses the effect of the mentioned parameters are investigated.
Keywords: Al-brasses; Microstructure; Surface; Corrosion potential; Microhardness